Environmental economics and natural resource management - Anderson, David A (Routledge, 2015)
The tools of environmental economics guide policymakers as they weigh development against nature, present against future, and certain benefits against uncertain consequences. From reluctant-but-necessary calculations of the value of life, to moral quandaries over profits at the environmentʹs expense, the models and findings explained in this textbook are relevant to todayʹs more pressing dilemmas. The third edition of Environmental Economics and Natural Resource Management retains the application-based narratives and visual emphasis of the second edition, while covering the latest policy initiatives, following recent trends, and becoming even more user friendly. An expanded array of color photographs, diagrams, and other visual aids provide new perspectives on global environmental and resource issues. The book covers topics including: a- efficiency and cost-benefit analysis; b- natural resource management; c- globalization; d- environmental ethics; and e- population growth and poverty. -- Back cover.